Heterologous Biosynthesis of Fungal Indole Sesquiterpene Sespendole. (19th June 2018) - Kudo, Kosei; Liu, Chengwei; Matsumoto, Tomoyuki; Minami, Atsushi; Ozaki, Taro; Toshima, Hiroaki; Gomi, Katsuya; Oikawa, Hideaki
Abstract: Indole sesquiterpene sespendole, which has been isolated from the filamentous fungus Pseudobotrytis terrestris FKA‐25, is a specific inhibitor of lipid droplet synthesis in mouse macrophages. The biosynthetic pathway that involves genes encoding six enzymes ( spdEMBQHJ ) was elucidated through heterologous expression of spd genes in Aspergillus oryzae, biotransformation experiments, and in vitro enzymatic reactions with a recombinant protein, thereby revealing the mechanism underlying the characteristic modification on the indole ring, catalyzed by a set of prenyltransferase (SpdE)/cytochrome P450 (SpdJ) enzymes. Functional analysis of the homologous genes encoding these enzymes involved in the biosynthesis of lolitrem allowed a biosynthetic pathway for the bicyclic ring skeleton fused to the indole ring to be proposed. Abstract : Find the right path : The biosynthetic pathway of sespendole is elucidated through heterologous production, in vitro analysis, and biotransformation experiments. A unique chimeric prenyltransferase (SpdE) and a cytochrome P450 (SpdJ) are characterized as modification enzymes for the synthesis of the oxidated prenyl side chain on the indole ring.